DASAR DAN TUJUAN PELAYANAN PETUGAS PASTORAL GEREJA - Don Bosco Karnan Ardijanto (Bahasa Indonesia, 2018)
Every Catholic is called and sent to continue Christ’s mission in union with the Church. To realize her/his call, s(he) participates in pastoral ministries of local Church. In fact, most of them participate in pastoral ministries is not based on true motivation. This article wants to challenge pastoral ministers to purify their fundamental motivation in order to nourish the Mystic Body of Christ. It also suggests them to cooperate with each other in their pastoral ministries.